Metal‐Free Catalytic Hydrogenolysis of Silyl Triflates and Halides into Hydrosilanes. Issue 23 (5th April 2022) - Durin, Gabriel; Fontaine, Albane; Berthet, Jean‐Claude; Nicolas, Emmanuel; Thuéry, Pierre; Cantat, Thibault
Abstract: The metal‐free catalytic hydrogenolysis of silyl triflates and halides (I, Br) to hydrosilanes is unlocked by using arylborane Lewis acids as catalysts. In the presence of a nitrogen base, the catalyst acts as a Frustrated Lewis Pair (FLP) able to split H2 and generate a boron hydride intermediate capable of reducing (pseudo)halosilanes. This metal‐free organocatalytic system is competitive with metal‐based catalysts and enables the formation of a variety of hydrosilanes at room temperature in high yields (>85 %) under a low pressure of H2 (≤10 bar). Abstract : The metal‐free hydrogenolysis of silyl triflates and halides into hydrosilanes is unlocked. This is enabled by the use of boron‐based organocatalysts that are competitive with metal catalysts.